2017
DOI: 10.15761/ecv.1000111
|View full text |Cite
|
Sign up to set email alerts
|

Corneal transplant failure associated with smoking

Abstract: This retrospective study was conducted in the University of Missouri's cornea transplant service from January 1, 2010 to September 30, 2015 to determine whether smoking increases the risk of corneal transplant failure. Cornea transplant patient's records were identified via the Informatics for Integrity Biology and the Bedside data query portal using the ICD-9 codes for penetrating keratoplasty (11.64), endothelial keratoplasty (11.62, 11.63 and 11.69) and 996.51 for corneal transplant failures. A total of 257… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Here, smoking lead to a significantly higher risk of developing Fuchs' endothelium corneal dystrophy with OR = 1.36 (p = 0.02) in the univariate analysis and OR = 1.30 (p = 0.047) in the multivariate analysis (Zhang et al 2013). Fraunfelder et al (2017) reported higher transplant failure rates in smokers compared to non-smokers after endothelial transplantation (Fraunfelder et al 2017). These findings provide further strength to the hypothesis that a clinically significant impact of smoking on corneal health should be expected in those with a priori poor corneal prognosis.…”
Section: Discussionmentioning
confidence: 92%
“…Here, smoking lead to a significantly higher risk of developing Fuchs' endothelium corneal dystrophy with OR = 1.36 (p = 0.02) in the univariate analysis and OR = 1.30 (p = 0.047) in the multivariate analysis (Zhang et al 2013). Fraunfelder et al (2017) reported higher transplant failure rates in smokers compared to non-smokers after endothelial transplantation (Fraunfelder et al 2017). These findings provide further strength to the hypothesis that a clinically significant impact of smoking on corneal health should be expected in those with a priori poor corneal prognosis.…”
Section: Discussionmentioning
confidence: 92%